Physical impairments of monitoring trails in all optical transparent networks. Issue 4 (1st December 2013) - Hosszu, Éva; Moghaddam, Ehsan Sarvghad; Tapolcai, János; Mazroa, Dániel
Abstract : In recent years, following the deployment of wavelength division multiplexing networks, fault detection and localisation has become a challenging issue in networks with high reliability. Optical layer monitoring schemes based on monitoring trails ( m ‐trail) are considered an efficient way to localise a single fault unambiguously in all‐optical networks. In spite of the extensive work on the m ‐trail concept, the issue has not been validated from the feasibility point of view. Previous works on the m ‐trail monitoring scheme have focused mainly on algorithm design for minimising the number of monitors, however, none of them have observed that length limitations should be considered as well. The authors investigate the physical constraints of launching m ‐trails, mainly focusing on the maximum length that each m ‐trail may have and describe an algorithm that solves the length constrained m ‐trail formulation problem. Numerous simulations were implemented in a physical layer simulator for observing qualitative parameters in different m ‐trail lengths. The authors propose 15 000 km as a length limit for each m ‐trail for out‐of‐band monitoring. Finally, an algorithmic solution is provided for monitoring trail design problem satisfying these physical constraints.